1984
DOI: 10.1104/pp.76.3.647
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Monoterpenes

Abstract: Previous studies have shown that the monoterpene ketone I-(G_3HJ menthone is reduced to the epimeric alcohols i-menthol and d-neomenthol in leaves of flowering peppermint (Menthapiperita L.), and that a portion of the menthol is converted to menthyl acetate while the bulk of the neomenthol is transformed to neomenthyl-,6-Dglucoside which is then transported to the rhizome (Croteau, Martinkus 1979 Plant Physiol 64: 169-175). Analysis of the disposition of I-(3Hjmenthone applied to midstem leaves of intact flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
1

Year Published

1985
1985
2002
2002

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 19 publications
1
12
1
Order By: Relevance
“…Previous investigations have indicated that peppermint monoterpenes can be metabolically degraded at later stages of leaf development (Croteau, 1988). A catabolic pathway was described involving the sequential reduction and glucosylation of menthone to neomenthol glucoside (Croteau and Martinkus, 1979), which is transported to the rhizome and degraded (Croteau et al, 1984;Croteau and Sood, 1985). Although the present study provided no evidence for monoterpene catabolism, the large variances in monoterpene incorporation after pulse labeling (Fig.…”
Section: Rate Of Monoterpene Loss Is Negligible Throughout Leaf Develcontrasting
confidence: 47%
“…Previous investigations have indicated that peppermint monoterpenes can be metabolically degraded at later stages of leaf development (Croteau, 1988). A catabolic pathway was described involving the sequential reduction and glucosylation of menthone to neomenthol glucoside (Croteau and Martinkus, 1979), which is transported to the rhizome and degraded (Croteau et al, 1984;Croteau and Sood, 1985). Although the present study provided no evidence for monoterpene catabolism, the large variances in monoterpene incorporation after pulse labeling (Fig.…”
Section: Rate Of Monoterpene Loss Is Negligible Throughout Leaf Develcontrasting
confidence: 47%
“…1) (16). The lactone, in turn, is metabolized to several unidentified nonvolatile polar and nonpolar products.…”
mentioning
confidence: 99%
“…In peppermint root, a sufficient number of metabolites, formed subsequent to the lactonization of the monoterpene ketone, could be identified to permit elucidation of a degradative pathway (12,13) (24,25). The microbial pathway also involves lactonization as a means of carbon ringopening (24,25), but further details ofthis pathway are presently unclear (20).…”
mentioning
confidence: 99%
“…The decline in content of the monterpene ketone (-)-menthone in the leaf oil of peppermint (Mentha piperita) has been shown to result from the enzymic reduction of the ketone to (+)-neomenthol, followed by glucosylation of this alcohol and subsequent transport ofthe resulting fl-D-glucoside from leaves to roots (11). On reaching the rhizome and roots, the glucoside is hydrolyzed, the aglycone oxidized ' back to (-)-menthone, and this ketone converted to (-)3,4-menthone lactone (13). The lactone undergoes a modified #-oxidation sequence at this site, analogous to that employed by microorganisms in the degradation of acyclic terpenoids (2), to yield acetyl CoA and reduced pyridine nucleotides which are subsequently utilized in the biosynthesis of acyl lipids and phytosterols of the root membranes (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation